Exploring Experiences and Academic Outcomes of First-Year University Students with and without Perceived Disabilities or Impairments. Issue 5 (3rd September 2022) - Murray, Amy; Sotardi, Valerie
ABSTRACT: The current study was conducted to understand better the university experiences and academic outcomes for students with and without self-reported disabilities or impairments. The project explored responses to an online questionnaire on early university experiences of first-year students ( n = 1019) within one New Zealand university. A cross-sectional design was used to explore patterns in academic self-perceptions, subjective well-being, and GPA between groups who categorised themselves as having or not having a disability, impairment, or long-term condition (yes or no) and those who were or were not registered with the institution's disability support service. Our results provide initial evidence that non-registered students with disabilities reported higher university-related anxieties and lower academic outcomes when compared to registered students with disabilities and students with no perceived disabilities. Well-being and academic self-efficacy did not significantly differ across the groups. The discussion section focuses on possible challenges that may arise for non-registered students with disabilities at university and possible future directions.